HALF-CASTE’S STATE OF LIMBO IN KATHARINE SUSANNAH PRICHARD’S “MARLENE” AND “FLIGHT” (1967) - Laily Ramadhani; Mamik Tri Wedawati (Ma Chung Press, 2021)
Half-caste refers to the mixed-blood in Australia who suffer much in their lives. They are not a part of Aborigines nor the Whites. They are not accepted by everyone and being mistreated. They suffer from unfair treatment and are also incapable of making decisions to get a better life. The purpose of the study is to reveal the state of limbo of the half-caste in Katharine Susannah Prichard’s “Marlene” and “Flight” (1967). The method used is qualitative by applying Wilson Harris’ state of limbo theory on the post-colonialism approach. Limbo is a transition where a person or community belongs in two contexts. There are three characteristics of limbo that are needed to be analyzed in the chosen literary work; anxieties, questions, and conflicts that every person or community cannot embrace. As a result, “Marlene” and “Flight” each have three characters of limbo. “Marlene” demonstrates the half-caste’s disrespectful life by being locked in the camp and not able to decide on making their life better. “Flight” demonstrates the three half-caste children that are taken forcedly to the Aborigines Protection Board. These children are locked in the room of the carrier so that they will not run away. Stuck in the camp, locked in the room, and unable to do anything to make their life better defines the limbo state of the half-caste’s lives.